Respiratory symptoms, lung function, and pneumoconiosis among self employed dental technicians. Issue 5 (May 1993) - Choudat, D; Triem, S; Weill, B; Vicrey, C; Ameille, J; Brochard, P; Letourneux, M; Rossignol, C
Abstract : From the registry of self employed workers living in Paris, a group of 105 dental technicians was studied to evaluate occupational exposure, to determine respiratory manifestations, and to investigate immune disturbances. Seventy one dental technicians (age range 43-68: group D), 34 dental technicians younger than 43 or older than 68 (group d), and 68 control workers (age range 43-66: group C) were investigated. The demographic characteristics and the smoking habits of the groups D and C did not differ significantly. The dental technicians often worked alone (43.7%) or in small laboratories without adequate dust control. The mean duration of their exposure was long (group D 34.0 (SD 8.4) years). The prevalence of respiratory symptoms did not differ between groups D and C except for the occurrence of increased cough and phlegm lasting for three weeks or more over the past three years (group D 16.9%, group C 2.9%, p < 0.007). The effect of cigarette smoking on respiratory symptoms and lung function was obvious. All mean values of lung function for dental technicians and controls were within normal limits. Significant decreases in all mean lung function values were found among smokers by comparison with non-smokers, however, and a positive interaction with occupational exposure was established. The x ray films of dental technicians (n = 102, groups D and d) were read independently by four readers and recorded according to the International Labour Office classification of pneumoconioses. The prevalence of small opacities greater than 1/0 was 11.8% with a significant increase with duration of exposure. The prevalence among dental technicians with 30 years or exposure or more was significantly higher (22.2%) than those with less than 30 years (3.5, p < 0.004). The prevalence of autoantibodies (rheumatoid factors, antinuclear antibodies, and antihistone antibodies) was not significantly different in the groups D and C. When positive, autoantibodies only occurred at low concentrations. This finding contrasts with previous reports on the occurrence of autoantibodies and even of connective tissue diseases in dental technicians. In conclusion, the study confirms an increased risk of pneumoconiosis among dental technicians. Moreover, there may be other lung disorders such as impairment of lung function especially in association with cigarette smoking.